Pemanfaatan Teknologi Augmented Reality Untuk Pengenalan Jaringan Tumbuhan Berbasis Android - Dwi Bintang Rabani; Zakariyah, Muhammad (STMIK Budi Darma, 2024)
In the world of learning, students' interest in learning is decreasing because they are still using a book media learning system that only contains images and text. Learning systems using text and images seem boring. In the world of education, the use of augmented reality technology as an alternative learning media for students. AR technology makes it easier for users to understand because the 3D objects displayed are more interesting and easy to understand. With marker-based method in augmented reality marker or two-dimensional object marker as a marker that will be read by the camera. The research method applied involves a series of stages that include system analysis, system design, implementation, and testing. From the problems that have been mentioned and the solutions provided by providing the creation of augmented reality applications can help teachers and students regarding learning with new learning methods. the development of applications that I make is expected that students can better understand the learning process. With the development of augmented reality plant tissue recognition applications, Augmented Reality (AR) in strengthening interactive learning experiences for its users. This shows that AR has the ability to change the learning paradigm by providing a more dynamic and interesting experience for users.